Tax Morale, Eastern Europe and European Enlargement - Torgler, Benno (2012)
This study tries to remedy the current lack of tax compliance research analyzing tax morale in 10 Eastern European countries that joined the European Union in 2004 or 2007. By exploring tax morale differences between 1999 and 2008, it shows that tax morale has decreased in 7 out of 10 Eastern European countries. This lack of sustainability may support the incentive based conditionality hypothesis that the European Union only has a limited ability to influence tax morale over time. The author observes that events and processes at the country level are crucial to understanding tax morale. Factors such as perceived government quality and trust in the justice system and the government are positively correlated with tax morale in 2008.